2010
DOI: 10.1177/039463201002300107
|View full text |Cite
|
Sign up to set email alerts
|

Beta2-Glycoprotein I is a Target of T Cell Reactivity in Patients with Advanced Carotid Atherosclerotic Plaques

Abstract: Evidence in animal models that beta2-glycoprotein I (beta2GPI), the principal target of autoimmune antiphospholipid antibodies, is involved in the initiation and progression of atherosclerosis, prompted us to investigate the possible role of this self protein as a target autoantigen of immune reactions in patients with carotid atherosclerosis. Plaque-infiltrating T lymphocytes from patients, and circulating T lymphocytes from patients and healthy subjects were tested by cell proliferation assay and by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The signal peptide [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] is underlined in the figure. The protein was further subjected to PROSITE and ASC analyses (see "Bioinformatic analysis"), which indicated that the following cysteine residues are likely to be involved in disulfide bond formation and to be responsible for the Sushi domain secondary structure: C23-C66, C51-C79, C84-C124, C110-C137, C142-C188, C174-C200, C205-C248, and C234-C260.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The signal peptide [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] is underlined in the figure. The protein was further subjected to PROSITE and ASC analyses (see "Bioinformatic analysis"), which indicated that the following cysteine residues are likely to be involved in disulfide bond formation and to be responsible for the Sushi domain secondary structure: C23-C66, C51-C79, C84-C124, C110-C137, C142-C188, C174-C200, C205-C248, and C234-C260.…”
Section: Resultsmentioning
confidence: 99%
“…This Th2 bias is consistent with the presence of ␤ 2 GPI-autoreactive T cells with a Th2 profile determined in the peripheral blood of patients with APS 14 and in patients with advanced carotid atherosclerotic plaques. 17 In addition, G-␤ 2 GPI enhanced the capacity of DCs to stimulate T-cell proliferation in an allogenic mixed-lymphocyte reaction. Further studies will be needed to verify whether protein glycation may modify DC uptake and presentation of ␤ 2 GPI, thus inducing Tand B-cell immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various cellular anti-self responses are mediated by chronic over-expression of tumor necrosis factor (14), along with some other cytokines as key factors in autoimmune processes. Mice that lack mast cells (W/Wv mice) are resistant to inflammatory and erosive arthritis induced by arthritogenic serum (41)(42)(43).…”
Section: Mast Cells (Mcs) and Tnfamentioning
confidence: 99%